Seed Germination Response of Nicotiana rustica L. (Solanaceae) to Salt Stress - Kheloufi Abdenour; Mansouri Lahouaria Mounia (Contemporary Agriculture)
Nicotiana rustica L., an economically important plant species cultivated for medicinal and industrial purposes, remains understudied in terms of seed germination dynamics under salinity stress. This study examines six key germination attributes, including final germination percentage (FGP), mean germination time, time to 50% germination, seedling length, germination tolerance index, and seed vigor index, over a period of seven days. This study investigates the influence of varying concentrations of sodium chloride (NaCl), ranging from 0 mM to 300 mM, on the germination kinetics of Nicotiana rustica seeds. The results reveal a significant effect of salinity on N. rustica germination, with increasing NaCl concentrations leading to reductions in FGP, delayed germination kinetics, inhibited seedling growth, and compromised seed vigor and tolerance. N. rustica seeds demonstrated a moderate sensitivity, with FGP declining from 99.3% at 0 mM NaCl to 7.66% at 300 mM NaCl. Statistical analysis confirmed these trends, showing highly significant differences (p < 0.001) among NaCl treatments for all germination traits. These findings improve our understanding of the physiological responses of N. rustica to salinity stress and highlight the importance of developing strategies to mitigate the adverse effects of salinity on seed germination and crop productivity.